The Influence of Extrinsic Motivation and Cross-Cultural Adjustment on Foreign Worker Commitment: The Mediating Role of Cross-Cultural Adjustment and Moderating Role of Employer Trust - Binti Ramli, Amelia; Azzah Said, Dr. Noor (Information Management and Business Review, 2024)
Palm oil is a key income source in Malaysia, with the industry heavily reliant on foreign workers. This reliance necessitates a focus on their welfare to address workforce shortages. This study examines the relationship between extrinsic motivation and organizational commitment, mediated by cross-cultural adjustment and moderated by employer trust among foreign workers. This study employed a quantitative research design, using SPSS for data analysis, and surveyed 242 foreign workers from companies listed on the Malaysian Palm Oil Council (MPOC) website in 2022, achieving a 100% response rate. The key findings show that organizational commitment positively influences extrinsic motivation, with cross-cultural adjustment significantly enhancing both. Employer trust moderates the relationship between organizational commitment and cross-cultural adjustment, underscoring its importance in cultural adaptation and motivation. These insights highlight the need for targeted strategies to improve job satisfaction and retention among foreign workers by addressing extrinsic motivational factors and cultural adaptation challenges. The research contributes to the literature by detailing the interplay of organizational factors and cultural adaptation in shaping motivational outcomes, suggesting future research to explore longitudinal studies and other moderating variables. These findings offer valuable implications for improving workforce performance and retention strategies in the palm oil industry.